Evaluation of three pinto bean varieties under drought and irrigation in Durango, Mexico. - Aurelio Pedroza-Sandoval (Agronomía Mesoamericana, 2015)
The aim of this study was to identify the behavioral response in growth and physiology on three bean varieties under irrigation and drought. The study was conducted in 2014 at the experimental campus from the Autonomous University of Chapingo, Regional University Unit of the Arid Zones, Durango, Mexico. A randomized block design with three replications in a split plot arrangement was used. The plots were the soil moisture contents: favorable, near to Field Capacity (FC: 22-26%) and unfavorable, near to Permanent Wilting Point (PWP: 16-20%); subplots were varieties of beans: Pinto Centauro, Pinto Americano, and Pinto Saltillo. The variety Pinto Centauro had the greatest plant height (10.2 cm), vegetation cover (155.1 cm2), and dry matter production per plant (5.2 g) and, physiologically, it showed an outstanding water use efficiency (15.8 μmol CO2: μmol H20). The variety Pinto Americano was the most stable in growth and development when changing from the favorable moisture condition (CC) to the hydric stress condition (PWP), which makes it more viable under restrictive water availability conditions, but also more susceptible to root rot, associated to soil pathogens.